Non-dominant leg induced changes on the three dimensional kinematics of 400 meters hurdle clearance - Valamatos, M.-J.; Valamatos, M.-Jo.; Veloso, A.; Santos, P. M.-H. (Book of Abstracts - 9th Annual Congress European College of Sport Science, July 3-6, 2004, Clermont-Ferrand, France, 2004)
The 400 meters hurdle running is very demanding in technical terms, involving a velocity effort at maximum intensity, which requires an excellent level of hurdles clearance technique (McFarlane, 1980 e 2000; Brown, 1992; Kerr, 1992). During this running event ten hurdles have to be clear, some of them with a non-dominant leg. To maintain the best performance during entire running, the athlete should try to stabilize his individual clearance technique, to use both dominant and non-dominant legs. The purpose of this study was to investigate kinematics changes on the hurdles clearance technique induced by the use of non-dominant leg as a lead leg. Method Nine national elite male athletes (body mass 73.17±5.78 Kg; height 1.83±0.06 m; age 24.89±5.49 years old; 400 mH best 51.28±1.76 s) participated in this study. The performance of the clearance action was video recorded at 100 Hz, using four video cameras (Panasonic GRDVL9800). Three dimensional coordinates of the athlete body joints were calculated using the DLT algorithm. Linear and angular displacement and velocity parameters were calculated. Total body centre of mass (BCM) was estimated using Zatziorsky and Selianov (1983) model. These procedures were repeated for the dominant and non-dominant leg. The differences between both conditions were tested using T-Tests for paired samples. Results Table 1 presents the kinematics parameters observed in performance of the Dominant and Non-Dominant Leg. When the athletes use the non-dominant leg, there was a decrease of the horizontal velocity of the centre of gravity (CG) (p<0.001), which was accompanied by a significant increase of the breaking phase on the both the take off and landing phases. Discussion/Conclusion The use of the non dominant leg caused a significant reduction on the horizontal velocity of the BCM and an increase in both the total clearance time and horizontal velocity loss. When the athletes use the non-dominant leg, there was an increase of the take-off contact time, due to a significant increase of both breaking and propulsive contact times. This increase of the breaking phase was due to a significant increase in the touchdown angle, associated to an excessive vertical displacement of the CG. This originated a substantial reduction of the horizontal velocity of the BCM. In line with these results, the landing angle increased, causing a longer landing time. These results allowed us to conclude that the athlete`s clearance technique was affected, and the knowledge of the main changes in the athlete`s technique could help the coach on their training processes.